The financial impact of the COVID-19 pandemic on the private healthcare industry in Malaysia - Omar, Elisa Nadia (2024)
The COVID-19 pandemic had first emerged in Malaysia in early 2020 and Malaysia had forced the Malaysian Government to implement various lockdown measures to curb the spread of the infection. As the Malaysian public healthcare system is over-stressed with exceeding capacities and increasing fatalities, the private healthcare system in Malaysia is said to have an opportunity to benefit from this crisis. Based on the research conducted on the private healthcare system, particularly the healthcare products and services, pharmaceuticals and healthcare provider subsectors, it is found that the healthcare products and services subsector profited the most during the pandemic due to the rising demand on gloves while the other subsectors were negatively impacted, albeit not as significantly as other sectors. Research found that the healthcare market makes a swift return to normalcy during the recovery period, save for companies which have strategies which heavily relied on the pandemic to profit from, such as Pharmaniaga Berhad. Recommendations are made to reduce the reliance of these healthcare companies on single-source revenue or streams and single regional market to diversify their business for continued growth and sustainability.